Diversity in Education Study (DivES): Investigating a neurodiversity module in higher education. - Amy J Schwichtenberg; Katherine Mirah; Amy Janis; Moon West; Annabelle L Atkin (PLoS ONE)
Roughly 20% of adults identify as neurodivergent - an umbrella term used to describe cognitively atypical individuals. Neurodivergent identities manifest in several forms including autism, attention dysregulation hyperactivity disorder/attention deficit hyperactivity disorder, dyslexia, and other cognitively atypical trajectories. Despite a societal increase in acknowledgment and awareness of neurodiversity, there remains little to no discussion or critical understanding of neurodivergent individuals, especially within the realm of higher education (HE). The aim of this study, as part of the Diversity in Education Study (DivES), is to explore the impact of a neurodiversity-focused module within the college classroom. This study included 153 students (predominantly female, heterosexual, third-year students, with white/European racial heritage); wherein, a neurodiversity-focused module was taught within the context of an undergraduate course on diversity. Pre (start of the term) and post (end of the term) surveys were compared to evaluate the impact of the module on student understanding of the term neurodiversity, self-endorsements of a neurodivergent identity, and critical consciousness of ableism. In sum, the neurodiversity-focused module increased neurodiversity awareness and self-endorsements but did not positively shift critical consciousness of ableism scores. Replication in larger and more diverse samples is needed before pedagogy recommendations may be solidified but this study provides preliminary support for the incorporation of a neurodiversity module within diversity-focused HE courses.